The Analysis of the Effect Allowance for Impairment Losses And Profitability on Bank Capital After the Adoption of PSAK 71 - Farhan Zaki; Sudrajat Sudrajat (Yayasan Riset dan Pengembangan Intelektual, 2023)
The purpose of this research is to determine the influence of the implementation of PSAK 71 on the conventional commercial bank capital. This study aims to understand how the Expected Credit Loss calculation method on CKPN affect to CAR. Additionally, this research aims to investigate the ROA on the increase in bank capital that is influenced by the rise in CKPN due to earning asset formation, following the adoption of PSAK 71. The research use the purposive sampling method to select 55 samples of conventional commercial banks registered with the OJK. The findings of this research indicate that the increase of CKPN due to the changes brought by PSAK 71 in the bank's CAR is not statistically significant. Furthermore, the results also demonstrate that the ROA of the bank doesn’t have a significant influence on the increase in the CAR of the bank. The outcomes of this research provide insights to the bank management, allowing them to more caution in extending bank credit to mitigate non-performing loans and maintain CKPN stability. Consequently, banks can maximize the profitability. The results of this study is to contribute to understanding of PSAK 71, particularly CKPN implementation's impact on bank capital through statistical tests.